Somatic musculature of Tardigrada: phylogenetic signal and metameric patterns. (11th October 2013) - Marchioro, Trevor; Rebecchi, Lorena; Cesari, Michele; Hansen, Jesper Guldberg; Viotti, Giulia; Guidetti, Roberto
Abstract : Although studies describing molecular‐based phylogenies within tardigrades are now frequently being published, this is not the case for studies combining molecular and morphological characters. Tardigrade phylogeny is still based, from a morphological point of view, almost exclusively on chitinous structures and little attention has been given to detecting and using novel morphological data. Consequently, we analysed the musculature of seven tardigrade species belonging to the main phyletic lines by confocal laser scanning microscopy and compared these morphological results with new molecular analyses (18S+28S rRNA genes). Finally, we analysed all the data with a total evidence approach. A consilience in the phylogenetic relationships among orders and superfamilies of tardigrades was obtained among the evolutionary trees obtained from morphological, molecular and total evidence approaches. Comparative analysis on the musculature allowed the identification of serial homologies and repeated metameric patterns along the longitudinal animal body axis. A phenomenon of mosaic evolution was detected in musculature anatomy, as dorsal musculature was found to be highly modified with respect to the other body muscle groups, probably related to the evolution of dorsal cuticular plates. An understanding of tardigrade musculature anatomy will give fundamental information to understand the evolution of segmental pattern within Panarthropoda. © 2013 The Linnean Society of London